Design, content validity, and inter-observer reliability of the ‘Digitization of Cultural Heritage, Identities, and Education’ (DICHIE) instrument - Ortega-Sánchez, Delfín; López-Sanvicente, Amparo Bernal (Humanities & social sciences communications, 2023)
The present study, on the one hand, seeks to offer the validated design of the Digitization of Cultural Heritage, Identities and Education (DICHIE) instrument, applicable in focus-group contexts, to extract qualitative data on both the needs and the challenges relating to the digitization of the cultural heritage of Castile and Leon (Spain). On the other hand, it aims to facilitate the contribution of solutions within the field of education and cultural policy for the cultural heritage within this Autonomous Community. The research adheres to quantitative-descriptive methodological principles and, in particular, follows instrumental psychometric studies of reliability and content validity. The results of the instrument were optimal, both in terms of internal reliability and complete global and intra-group content validity, for its application to professional areas of heritage conservation and education and digital cultural management.